Mexico Is Not Colombia Alternative Historical Analogies for Responding to the Challenge of Violent Drug-Trafficking Organizations, Supporting Case Studies - Paul, Christopher (RAND Corporation, 2014)
Despite the scope of the threat they pose to Mexico's security, violent drug-trafficking organizations are not well understood, and optimal strategies to combat them have not been identified. While there is no perfectly analogous case to Mexico's current security situation, historical case studies may offer lessons for policymakers as they cope with challenges related to violence and corruption in that country.